Effects of separate and combined estradiol and progesterone administration on fear extinction in healthy pre-menopausal women - Michael Kaczmarczyk; Christian Eric Deuter; Hanna Deus; Anna Kallidou; Christian J. Merz; Julian Hellmann-Regen; Christian Otte; Katja Wingenfeld (Translational Psychiatry)
Abstract Altered fear conditioning and extinction learning are discussed as key etiological features in anxiety disorders. Women have an increased risk for anxiety disorders and fear conditioning has been shown to be influenced by the menstrual cycle phase and circulating gonadal hormones. The objective of our study was to investigate the effects of separate and combined estradiol and progesterone administration on fear extinction in healthy women. We conducted a placebo-controlled, randomized study in healthy women, who completed a fear conditioning paradigm on three consecutive days: fear acquisition training on day 1, fear extinction training on day 2, and return of fear test on day 3. Skin conductance responses (SCRs) served as main outcome variable. Two hours before testing on day 2, participants received pills containing either placebo, estradiol (2 mg), progesterone (400 mg) or the combination of both. We examined 116 women (mean age 25.7 ± 6.0 years), who showed significantly stronger conditioned SCRs to the CS+ than CS- during fear acquisition training indicating successful fear learning. At the beginning of the fear extinction training, estradiol administration reduced the differentiation between the conditioned stimuli. In the return of fear test, the estradiol groups showed heightened SCR responses to the previously extinguished stimulus, i.e., impaired extinction recall. Administration of progesterone did not have any significant influence on SCRs. There were also no effects on fear potentiated startle response. In our interpretation, exogenous estradiol administration affected the extinction of the conditioned fear response which led subsequently to a stronger return of fear. From a clinical perspective our findings suggest that estradiol levels may have an influence on the success of exposure therapy and could be taken into consideration when planning exposure sessions.